ANALISIS KESALAHAN SISWA MA DALAM PEMECAHAN MASALAH MATEMATIKA REALISTIK MATERI BARISAN ARITMATIKA DAN GEOMETRI - septia, tika; M Misbahul Kiromi (LP3M IAI Al-Qolam, 2023)
This study aims to investigate students' errors in solving realistic mathematics problems involving arithmetic and geometric sequence materials. This study needs to be done to find out what mistakes students are making so that it can help discover answers to reduce the incidence of comparable errors in studying. The descriptive method with a qualitative approach is the research methodology used in this study. Three students acted as research participants. The data analyzed came from a written test in the form of an essay consisting of five essay questions. The data analysis conducted in this study is a qualitative data analysis consisting of data reduction, data presentation, and conclusions.